Two-Staged Cranial Reconstruction: Tissue Expansion, Galeocapsular Flaps, and CAD/CAM Three-Dimensional Titanium Implants - VURAL Y.; KOÇ C.; AYSAL B. K.; YILDIZ K. (My University, 2026)
Reconstruction of cranial defects after prior surgery remains aesthetically and technically challenging, particularly when osseous deficiency is accompanied by limited soft-tissue coverage. Recent advances in computer-aided design/computer-aided manufacturing have expanded the role of patient-specific implants in late cranial reconstruction and provided alternatives in cases in which revision osteotomy or repeat cranioplasty is not suitable. A 19-year-old male with residual cranial deformity after fronto-orbital advancement for unilateral anterior plagiocephaly underwent a 2-stage procedure. Imaging demonstrated frontal and parietal bone defects without increased intracranial pressure. A novel 2-stage reconstructive approach was planned to improve frontal projection and restore the frontoparietal contour. In the first stage, a 550-mL rectangular tissue expander was placed in the left parietal region and gradually expanded. In the second stage, a patient-specific titanium implant was designed using preoperative virtual planning based on contralateral anatomy and combined with a galeocapsular flap elevated from the expander capsule-galea complex. The implant corrected frontal and parietal depression as well as supraorbital retrusion, whereas the galeocapsular flap and expanded scalp provided vascularized soft-tissue coverage and enabled tension-free closure. At 12-month follow-up, cranial contour and frontal projection were satisfactory, with no complications including infection, wound dehiscence, implant exposure, or displacement. This 2-stage technique may represent a safe and effective option for selected patients requiring late cranial contour reconstruction after previous cranial surgery.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Otolaryngology; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Cerrahi; Clinical Medicine (Med); Clinical Medicine; Surgery; Otorhinolaryngology; CAD/CAM; cranioplasty; galeocapsular flap; late cranial reconstruction; tissue expander